KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU - Susanti, Dewi; Ifriqia, Fartika; Rois, Moh. (Institut Agama Islam Negeri Kediri, 2017)
Abstract: Forward the retreat of an educational institution is very influential on the leader figure. In the principal education institution has an important role to advance the school in the lead. Basically education consists of several components that affect each other and related to each other. Of these components, the teacher who plays an important role and is the key to the success of education. For that the competence of a teacher should be improved. With the principal component of teachers and principals that play an important role for the advancement of education, the authors are interested to explore the leadership of principals in improving teacher competence, with the focus of research: 1) How the principal’s efforts in improving teacher competence, 3) the principal’s efforts in improving teacher competence ?. From the research results can be concluded, that 1) Efforts principals in improving teacher competence. 2) Factors that support the principal’s efforts in improving teacher competence. 3) Principal inhibiting factors in improving teacher competence. Abstrak: Maju mundurnya suatu lembaga pendidikan sangat berpengaruh pada sosok pemimpin. Dalam lembaga pendidikan kepala sekolah mempunyai peran penting untuk memajukan sekolah yang di pimpinnya. Pada dasarnya pendidikan terdiri dari beberapa komponen yang saling berpengaruh dan berkaitan antara yang satu dengan yang lainnya. Dari komponen tersebut, gurulah yang memegang peran penting dan merupakan kunci pokok bagi keberhasilan pendidikan. Untuk itu kompetensi seorang guru harus di tingkatkan. Dengan adanya komponen kepala sekolah dan guru yang sangat berperan penting untuk kemajuan pendidikan, maka penulis tertarik untuk mendalami tentang kepemimpinan kepala sekolah dalam meningkatkan kompetensi guru, dengan fokus penelitian: 1) Bagaimana upaya kepala sekolah dalam meningkatkan kompetensi guru?, 3) Apa faktor penghambat usaha kepala sekolah dalam meningkatkan kompetensi guru?. Dari hasil penelitian dapat disimpulkan, bahwa 1) Upaya kepala sekolah dalam meningkatkan kompetensi guru. 2) Faktor yang mendukung usaha kepala sekolah dalam meningkatkan kompetensi guru. 3) Faktor penghambat usaha kepala sekolah dalam meningkatkan kompetensi guru.